2007
DOI: 10.1111/j.1365-2567.2007.02680.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumour immunity by combined use of temozolomide and TAT‐survivin pulsed dendritic cells in a murine glioma

Abstract: SummaryAlthough chemotherapy remains among the best treatment options for most cancers, adjuvant therapies such as dendritic cell (DC)-based immunotherapy have been added to treatment protocols to destroy residual tumour cells. Combination treatment with low-dose temozolomide (TMZ) chemotherapy followed by vaccination with TAT-survivin-pulsed DCs enhanced T-cell responses specific for survivin and improved survival rate, as compared with DC alone or TMZ alone. Moreover, antigen-specific immunity appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…The considerable immune response rate may, moreover, reflect a beneficial effect of temozolomide. Several studies in mice have reported enhanced immunization after combining vaccination with temozolomide, or that temozolomide suppresses Treg function (4,(36)(37)(38)(39)(40). Chemotherapy may also suppress myeloid-derived suppressor cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…The considerable immune response rate may, moreover, reflect a beneficial effect of temozolomide. Several studies in mice have reported enhanced immunization after combining vaccination with temozolomide, or that temozolomide suppresses Treg function (4,(36)(37)(38)(39)(40). Chemotherapy may also suppress myeloid-derived suppressor cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…Although some objective responses were observed with increased tumor-free survival, the current adjunctive approaches are not curative. Thus, movement toward testing several modalities involving combinations of chemotherapy coupled with specific TAA peptide-pulsed DC vaccines has occurred [16]. Despite the fact that factors influencing the host immune response are poorly understood at this time, DC vaccination has emerged as a promising type of active immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of multimodality treatments that combine conventional antitumor therapies with immunotherapy, such as vaccination with DC-based vaccines, has emerged as a potentially plausible approach to the treatment of tumors (3,5). We previously reported that the use of a multimodality treatment regimen with a DC-based vaccine in combination with the chemotherapeutic agent temozolomide (TMZ) leads to enhanced tumor-specific CTL responses and enhanced antitumor effects, resulting in a cure rate higher than that achieved with either a DC-based vaccine or TMZ alone (17,28). However, the immunological factors relating to the antitumor effect of TMZ chemoimmunotherapy in a murine glioma model are still unclear.…”
mentioning
confidence: 99%